A single centre experience of straight to test suspected UGI cancer service. (13th March 2011) - Gordon, V M; Madhotra, R; Steer, P
Abstract : Introduction: The NHS Plan in July 2000 gave cancer services a high priority and government backing for reform of cancer services in England. One of the aims was to promote early detection of cancer. This led to introduction of 2-week wait for diagnostics and 1 month from referral to treatment. Milton Keynes launched their new 2-week wait Straight To Test Service (STT) in April 2006 thus taking out unnecessary first new appointment. Methods: Analysed the information kept in secure database of all STT patients from April 2006 till mid November 2009. Evaluation of the last 100 consecutive referral proformas for appropriateness as per NICE guidelines was performed. The authors also undertook a patient satisfaction survey. Results: 1053 patients were referred to the service in total. 904 patients underwent an OGD. The remaining patients had an alternate test or appointment if OGD was thought inappropriate. 99.5% of patients were offered a test or appointment within 2 weeks of referral. Average time to test was 10 days regardless of whether the patient rearranged. 45% of patients were male and 55% female. 82.5% of patients were over 55. The mean age was 67. Most patients had dyspepsia as the presenting symptom. The commonest combination of symptoms was that of dyspepsia and weight loss. Of the OGD's performed 79% were abnormal versus 60% when previously audited. Overall 147 cancers (14%) were detected from 1053 patients. Of the 904 patients who had OGD 116 (12.8%) had cancers. Most of these were upper GI with the remainder found on further tests. 8% of patients who had an OGD had oesophageal cancer, 1.5% had gastric cancer and 0.1% had gastric lymphoma. Of the last 100 consecutive patients proformas that were assessed retrospectively for appropriateness 4% were inappropriate for 2-week wait but 3% of these needed a clinically urgent OGD, this is an improvement on previous audit (10.6%). Concerning follow-up; 51% were discharged to their GP after the initial test. Patient satisfaction questionnaire revealed overall 95% satisfaction of 60 patients who responded. A cost saving of £212 825 is estimated over 3.5 years that is £5000 a month in out-patient appointments. Conclusion: Overall there has been an improvement in the service since initiation. Milton Keynes General Hospital is able to achieve initial diagnostics within 2 weeks of referral in 99.5% of cases. There is a high diagnostic yield from the tests performed. Importantly the authors have managed to reduce the number of inappropriate OGD's likely as a result of an improved proforma being utilised which asks for more clinical information. The majority of their patients were satisfied. The authors have made a substantial saving in costs with this pathway. The authors wonder whether their experience would influence other Hospitals to use the same template for suspected UGI cancer.